A critical investigation on the incorporation of IBS knowledge into the Polytechnic academic curriculum [electronic resource] - Erita Mazwin Mazlan, 1976-; Fakulti Kejuruteraan Awam (2009)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2009